Tissue engineering approaches for the construction of a completely autologous tendon substitute - Bassetto Franco; Vindigni Vincenzo; Dalla Vedova; Carolin Tonello; Giovanni Abatangelo; Francesco Mazzoleni (Indian Journal of Plastic Surgery)
Tissue engineering is a multidisciplinary field that involves the application of the principles and methods of engineering and life sciences towards i) the fundamental understanding of structure-function relationships in normal and pathological mammalian tissues and ii) the development of biological substitutes that restore, maintain or improve tissue function. The goal of tissue engineering is to surpass the limitations of conventional treatments based on organ transplantation and biomaterial implantation. The field of tendon tissue engineering is relatively unexplored due to the difficulty in in vitro preservation of tenocyte phenotype. Only recently has mechanobiology allowed us to gain a better understanding of the fundamental role of in vitro mechanical stimuli in maintaining the phenotype of tendinous tissue. This review analyzes the techniques used so far for in vitro regeneration of tendinous tissue.